Blunt traumatic injuries of thoracic aorta, a retrospective study - Baldaia, Leonor (2024)
INTRODUCTION: Blunt thoracic aortic injuries (BTAI) are defined as a tear in the thoracic aorta caused by a high energy blunt trauma with sudden deceleration and increased intravascular pressure. The most common reported mechanism of injury is motor vehicle accidents, and it can be potentially lethal. The purpose of this study was to analyze and report our center’s experience in the treatment of blunt traumatic injuries of thoracic aorta and supra-aortic trunks. METHODS: A retrospective review of a single center's database was done to identify all patients treated for BTAI, in a four-year period, from January 2018 to December 2021. Follow-up period ranged from three to 24 months. Patients’ demographics, injury mechanism, location and grade of aortic injury, treatment details, timing of intervention, length of hospital stay, follow-up time, and postoperative morbidity and mortality were extracted from patients’ medical records. A descriptive analysis of all the data was performed. RESULTS AND DISCUSSION: We identified six patients to include in the study. Mean age was 29 years and 83.3% of patients were male. The mechanism of injury was motor vehicle accident for all cases. The most common injury grade was type III (pseudoaneurysm) in five patients (83.3%), and one patient presented with a type IV aortic injury with rupture. All injuries were in the aortic isthmus and all patients were suitable for TEVAR. Mean time to intervention was 17 days. Mean oversizing was 11%. Two patients had coverage of their LSA. No deaths occurred in the hospital or during the follow-up period, and there were no registered vascular procedure-related morbidities. CONCLUSION: This study reports a level one trauma center experience in management of BTAI. All patients underwent CTA for diagnosis and grading of aortic injury. TEVAR proved to be effective in the treatment of BTAI, with few complications and good outcomes at short and mid-term follow-up, and it should be the first-line treatment for these patients. OSR should be an option when a patient’s injury is not suitable for endovascular approach.